Structural Equation Modeling: Effect of VLE in Mathematics Learning (Interdisciplinary Research in Education, 2025)
This research analyzes the relationships amid Virtual Learning Environment (VLE) engagement, student learning engagement, student learning styles, and mathematics achievement. The focus has been given on both the process and result, using a Structural Equation Modeling (SEM). The data were collected from 126 master’s level students enrolled in a Differential Geometry course at university campus, Central Department of Education, in the academic year, 2017. The data was elicited by using the tools: mathematics achievement test (MAT), Felder-Silverman developed students learning style index (SLS), questionnaire for students perceive learning engagement (SLE), Moodle based VLE log data, and students final test score. As per the finding of the study, VLE engagement and Test score demonstrated an acceptable to good fit with following statistical value, CFI = 0.96, TLI = 0.93, RMSEA = 0.09, SRMR = 0.08, in which statistically significant factor loadings supported the observed variables’ representation of their latent constructs. The study has provided a foundation for further structural analysis, in measuring the constructs as model in educational contexts.